The Effectiveness of Online Teaching and Learning in Polman Bandung - Nia Nuryanti Permata; Dini Hadiani (SOSHUM : Jurnal Sosial dan Humaniora, 2021)
This article reports the effectiveness of online teaching and learning in a polytechnic institution. The online teaching and learning during the Covid19 pandemic have made a challenging situation. Moreover, the subjects or courses at Polman Bandung consist of the Theory course (e.g., Maths, English, Strength of Materials) and Practice course (e.g., Technical Drawing, CNC Machine practical program, Bench-work). What happens in the online classroom and its effectiveness should be known and considered by its academic officer. In general, the target to be achieved in this study is to provide an overview of online learning and measure online learning effectiveness in 2020. The research method used is a descriptive study. Data collection was done by distributing questionnaires to the third-grade students who have had or are currently implementing online learning in Theory and Practice courses. There were 231 questionnaire data collected. Besides, semi-structured interviews with students and lecturers were also carried out. The study results show that the teaching and learning effectivity carried online were scored in 3.25 by students (scale 1- 4), meaning it is still inadequate performance. Both Theory and Practice courses were challenging for students and lecturers, but the practice was considered more challenging. Some departments could not hold Practice courses entirely online due to the laboratory tools and machines needed. Therefore, it is recommended that the lecturer improve their online teaching skills and interact more with students in the Theory course and Practice course. The students should better communicate with the lecturers and, most importantly, handle significant learning challenges. Then, the institution should make a better system and program to help the lecturer to teach online.